Ultrasensitive quantum dot fluorescence quenching assay for selective detection of mercury ions in drinking water - Ke, J.; Li, Xin Yong; Zhao, Q.; Hou, Y.; Chen, J. (Nature Publishing Group, 2014)
Mercury is one of the most acutely toxic substances at trace level to human health and living thing. Developing a rapid, cheap and water soluble metal sensor for detecting mercury ions at ppb level remains a challenge. Herein, a metal sensor consisting of MPA coated Mn doped ZnSe/ZnS colloidal nanoparticles was utilized to ultrasensitively and selectively detect Hg 2+ ions with a low detection limit (0.1 nM) over a dynamic range from 0 to 20 nM. According to strong interaction between thiol(s) and mercury ions, mercaptopropionic acid (MPA) was used as a highly unique acceptor for mercury ions in the as-obtained ultrasensitive sensor. In the presence of mercury ions, colloidal nanoparticles rapidly agglomerated due to changes of surface chemical properties, which results in severe quenching of fluorescent intensity. Meanwhile, we find that the original ligands are separated from the surface of colloidal nanoparticles involving strongly chelation between mercury ion and thiol(s) proved by controlled IR analysis. The result shows that the QD-based metal ions sensor possesses satisfactory precision, high sensitivity and selectivity, and could be applied for the quantification analysis of real samples.